Community Participation and Water Quality in Supporting Sustainable Water-Based Tourism Management: A Case Study of Umbul Brintik, Indonesia - Rheno Ruswandari; Mochamad Arief Budiharjo; Yanuar Luqman (Journal of Bioresources and Environmental Sciences, 2025)
This study analyzes community participation and environmental quality in supporting sustainable water-based tourism management at Umbul Brintik, Klaten Regency, Indonesia. The research aims to assess the level of community participation across management stages, evaluate water quality as an indicator of environmental sustainability, and examine the integration between social participation and environmental governance in a community-managed tourism destination. An explanatory mixed-methods approach was employed, combining questionnaire surveys of local residents analyzed using a non-compensatory Community Participation Index (CPI), water quality assessment using the STORET method and the Water Quality Index (WQI), and in-depth interviews with key stakeholders. The findings indicate that community participation is generally high, with very high levels observed at the implementation, benefit-sharing, and evaluation stages, while participation at the planning stage remains comparatively lower. Water quality analysis shows that all physical, chemical, and biological parameters meet national standards, with STORET results indicating good water quality and WQI values classified as excellent. The integrated analysis reveals that although strong community participation coexists with favorable environmental conditions, environmental governance remains largely informal and lacks institutionalized mechanisms such as routine monitoring and formal environmental management procedures. This study demonstrates that high participation levels do not automatically ensure long-term environmental sustainability and highlights the need to strengthen participatory planning and institutionalize preventive environmental management to sustain community-managed water-based tourism destinations.